The Australian Management of Protected Underwater Cultural Heritage Artifacts in Public and Private Custody. Issue 3 (August 2022) - Viduka, Andrew; Luckman, Grant
Abstract: This article briefly outlines underwater cultural heritage artifact management in Australia from an unregulated collecting environment in the 1940s–1960s to the increasingly regulated environment of the present. In 1993, in conjunction with new legislation, an amnesty was declared in order to inventory artifacts collected from now-protected historic shipwrecks that were in private hands. The amnesty period concluded with approximately 20, 000 artifacts notified at a time when information was being stored in a range of formats and to different standards. Today, the Australian Government manages the possession, custody, and control of approximately 500, 000 underwater cultural heritage artifacts, most of which are in collecting institutions, with one-tenth in public custody. This article highlights the contemporary legislative, policy, and administrative framework for the management of underwater cultural heritage artifacts in Australia, particularly those that remain in the possession of private individuals and are subject to trade.